STRATEGI PEKERJA SOSIAL DALAM PANTI REHABILITASI WANITA TUNA SOSIAL BERBASIS PENGEMBANGAN USAHA DI KABUPATEN OGAN ILIR: STRATEGI PEKERJA SOSIAL DALAM PANTI REHABILITASI WANITA TUNA SOSIAL BERBASIS PENGEMBANGAN USAHA DI KABUPATEN OGAN ILIR - Wahidin; Dewi Kartika (Jurnal Ilmu Pekerjaan Sosial, 2023)
Abstract: The independence of beneficiaries at Sentra Mulya Jaya is a goal prioritized by the government in providing vocational training programs to prepare them for entrepreneurship at the Atensi Creation Center (SKA). The SKA program is a program that accommodates beneficiaries who have received vocational training to become entrepreneurs. This thesis discusses how the post-vocational social assistance training program influences the entrepreneurial independence of beneficiaries at the Atensi Creative Center. Then, this study discusses the condition of beneficiary independence from the aspects of emotional independence, behavioral independence, and value independence. This study has used a qualitative research method with a descriptive approach. The results of this study are: 1) The level of education influences the learning process of beneficiaries. 2) The ability of beneficiaries when setting targets does not contain elements of innovation and beneficiaries have intellectual independence so that they can solve the problems they face. 3) The beneficiary expects the assistant to help in innovating. 4) The regulations stipulated by the SKA are obstacles experienced by beneficiaries in carrying out innovations, this affects the behavioral autonomy of beneficiaries. Based on the research results, the researcher recommends that training instructors need to add variety in providing entrepreneurship material to beneficiaries who have low formal education; beneficiary assistants need to increase assistance in carrying out the process of monitoring and providing entrepreneurship guidance; The implications of this research can be used as an evaluation of vocational training programs at the Atensi Creation Center or similar places. The SKA coordinator needs to evaluate the regulations stipulated in SKA regarding sales regulations and SOPs. Key words: Social worker strategy, Rehab Institution, WTS business development.